2007
DOI: 10.1016/j.healthplace.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Placing the dynamics of syringe exchange programs in the United States

Abstract: Drawing upon the broader health, social, and political geography literature this paper outlines a framework for considering place-based processes through which syringe exchange availability may be understood. It is argued that the geographic distribution of syringe exchange programs (SEPs) in the United States is linked to the social and political conditions of particular localities through three place characteristics: (1) structural constraints; (2) social and spatial distancing of injection drug users; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
1
14
0
2
Order By: Relevance
“…Though concerns that SEPs increase crime rates and exposure to discarded syringes are unfounded, 76,77 the location of SEP sites remains controversial. [2][3][4] Our results support past research that has found that the presence of an SEP in a geographic area reduces HIV risk behavior among local residents who inject; 24-26 moreover, we find that this benefit extends to injecting residents who do not personally go to the SEP site.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Though concerns that SEPs increase crime rates and exposure to discarded syringes are unfounded, 76,77 the location of SEP sites remains controversial. [2][3][4] Our results support past research that has found that the presence of an SEP in a geographic area reduces HIV risk behavior among local residents who inject; 24-26 moreover, we find that this benefit extends to injecting residents who do not personally go to the SEP site.…”
Section: Discussionsupporting
confidence: 89%
“…This controversy often extends to the sites where SEPs operate. [2][3][4] Local business leaders and residents, for example, have protested the establishment and ongoing operation of SEPs in their midst. 3 The 2010 appropriations law that lifted the federal ban codified this controversy: the law stipulates that, to be eligible for federal funding, SEPs must first receive local police department and public health department approval on the location of their sites.…”
mentioning
confidence: 99%
“…This problem is compounded by the fact that small towns often provide little in the way of either services or alternate outlets for their populations of young, poor, underemployed or undereducated people. Even in more urbanized areas, attempts to provide services for drug users are shaped and challenged by strong resistance to the idea of drug users existing within particular places (Tempalski 2007).…”
Section: Discussionmentioning
confidence: 99%
“…L'épidémiologie nord-américaine a montré que l'usage des drogues illicites existe dans tous les types de quartier, mais les trajectoires des usagers, les risques encourus par la prise des drogues et les ressources pouvant contribuer à réduire les dommages causés par les modes de consommation, varient géographiquement. Ainsi, la visibilité de la consommation des drogues, susceptible d'enclencher un processus de stigmatisation de l'utilisateur (phénomène qui, à son tour, peut décourager la fréquentation de certains dispositifs et services de soins), est inégalement répartie selon les villes et les quartiers (Saxe, Kadushin et coll., 2001 ;Fuller, Borrell et coll., 2005 ;Tempalski, 2007). De même, les politiques de prévention et de réduction de risques (Tempalski, 2007 ;Feroni et Lovell, 1996), ainsi que la disponibilité et la nature de l'offre de soins en toxicomanie (Feroni, Paraponaris et coll., 2004), varient selon les villes et selon les quartiers.…”
Section: Drogues Santé Et Société Vol 7 N O 1 Juin 2008unclassified
“…Ainsi, la visibilité de la consommation des drogues, susceptible d'enclencher un processus de stigmatisation de l'utilisateur (phénomène qui, à son tour, peut décourager la fréquentation de certains dispositifs et services de soins), est inégalement répartie selon les villes et les quartiers (Saxe, Kadushin et coll., 2001 ;Fuller, Borrell et coll., 2005 ;Tempalski, 2007). De même, les politiques de prévention et de réduction de risques (Tempalski, 2007 ;Feroni et Lovell, 1996), ainsi que la disponibilité et la nature de l'offre de soins en toxicomanie (Feroni, Paraponaris et coll., 2004), varient selon les villes et selon les quartiers. La possibilité de se procurer des seringues stériles ou de choisir son lieu d'injection n'est pas la même dans des quartiers favorisés ou défavorisés socialement (Buchanan, Shaw et coll., 2003), et elle est tributaire également de certains aspects de l'organisation sociale, comme la structure familiale (Page et Salazar, 1999).…”
Section: Drogues Santé Et Société Vol 7 N O 1 Juin 2008unclassified